A Prediction Market-Based Gamified Approach to Enhance Knowledge Sharing in Organizations. (October 2019) - Mizuyama, Hajime; Yamaguchi, Seiyu; Sato, Mizuho
Background .Knowledge sharing among the members of an organization is crucial for enhancing the organization's performance. However, knowing how to motivate and direct members to effectively and efficiently share their relevant private knowledge concerning the organization's activities is not entirely a straightforward matter. Aim . This study aims to propose agamified approach not only for motivating truthful sharing and collective evaluation of knowledge among the members of an organization but also for properly directing those actions so as to maximize the usefulness of the shared knowledge. A case study is also conducted to understand how the proposed approach works in a live business scenario. Method . Aprediction market game on a binary event on whether the specified activity will be completed successfully is devised. The game utilizes an originalcomment aggregation and evaluation system through which relevant knowledge can be shared verbally and evaluated collectively by the players themselves. Players' behavior is driven toward a desirable direction with theassociated incentive framework realized by three game scores. Results . The proposed gamified approach was implemented as a web application and verified with a laboratory experiment. The game was also played by four participants who deliberated on an actual sales proposal in a real company. It was observed that the various valuable knowledge elements that were successfully collected from the participants could be utilized for refining the sales proposal. Conclusions . The game induced motivation through gamification, and some of the designed game scores worked in directing the players' behavior as desired. The players learned from others' comments, which brought about a snowball effect and enriched collective knowledge. Future research directions include how to transform this knowledge into an easy-to-comprehend representation.